Hypothesis: Silver Nanoparticles as an Adjuvant for Cancertherapy - Ramin Mohammadzadeh (Tabriz University of Medical Sciences, 2012)
Cytotoxic agents are a main part of therapeutic process against the observed tumors, which lead to some unwished damages, due to drug uptake by normal body cells causing various tissue/organ failures associated with formal administration manners. But nowadays the risk is reduced by new target therapy techniques, of which the observed physical nature of micelles and nanosilver particles, governing their special behavior, could help using micelle-coated silver nanoparticles as a novel adjuvant for cancer target therapy.